Frontispiece: Zwitterion/Brønsted Acid Mixtures Showing Controlled Lower Critical Solution Temperature‐Type Phase Changes with Water. Issue 35 (12th August 2016) - Mieno, Yuki; Kohno, Yuki; Saita, Shohei; Ohno, Hiroyuki
Abstract : Zwitterion Brønsted Acid Mixture An ammonium‐type zwitterion was designed to show a lower critical solution temperature‐type phase behavior with water after mixing an equimolar amount of trifluoromethanesulfonic acid, a typical Brønsted acid. This type of aqueous two‐phase system affords diverse applications upon considering their combination of properties, such as thermoresponsiveness and acid functionality. Potential applications include novel catalytic reaction/product separation systems. For more details, see the Communication by H. Ohno et al. onpage 12262 ff.